A Systems Approach to Evaluate One Health Initiatives - Rüegg, Simon R.; Nielsen, Liza Rosenbaum; Buttigieg, Sandra C.; Santa, Mijalche; Aragrande, Maurizio; Canali, Massimo; Ehlinger, Timothy; Chantziaras, Ilias; Boriani, Elena; Radeski, Miroslav; Bruce, Mieghan; Queenan, Kevin; et al. (Frontiers in Veterinary Science, 2018)
Challenges calling for integrated approaches to health, such as the One Health (OH) approach, typically arise from the intertwined spheres of humans, animals and ecosystems constituting their environment. Initiatives addressing such wicked problems commonly consist of complex structures and dynamics. As a result of the EU COST Action (TD 1404) “Network for Evaluation of One Health” (NEOH), we propose an evaluation framework anchored in systems theory to address the intrinsic complexity of OH initiatives and regard them as subsystems of the context within which they operate. Typically, they intend to influence a system with a view to improve human, animal and environmental health. The NEOH evaluation framework consists of four overarching elements, namely: (1) the definition of the initiative and its context, (2) the description of the theory of change (TOC) with an assessment of expected and unexpected outcomes, (3) the process evaluation of operational and supporting infrastructures (“the One Health-ness”), and (4) an assessment of the association(s) between the process evaluation and the outcomes produced. It relies on a mixed methods approach by combining a descriptive and qualitative assessment with a semi-quantitative scoring for the evaluation of the degree and structural balance of “One-Health-ness” (summarised in a OH-index and OH–ratio, respectively) and conventional metrics for different outcomes in a multi-criteria-decision-analysis. Here we focus on the methodology for Elements (1) and (3) including ready-to-use Microsoft Excel spreadsheets for the assessment of “the One-Health-ness”. We also provide an overview of Element (2), and refer to the NEOH handbook for further details, also regarding Element (4) (http://neoh.onehealthglobal.net). The presented approach helps researchers, practitioners and evaluators to conceptualise and conduct evaluations of integrated approaches to health and facilitates comparison and learning across different OH activities thereby facilitating decisions on resource allocation. The application of the framework has been described in eight case studies in the same Frontiers research topic and provide first data on OHI and OHR, which is an important step towards their validation and the creation of a dataset for future benchmarking, and to demonstrate under which circumstances OH initiatives provide added value compared to disciplinary or conventional health initiatives.